Prediction of Atonic Postpartum Hemorrhage (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The aim of our study was to retrospectively examine the history of childbirth and the quality of primary care for bleeding and evaluate the prescribed rehabilitation measures for women who have suffered postpartum hemorrhage and massive bleeding. The materials and methods of the study were 242 birth histories with postpartum hemorrhage for the last 6 years (2013-2018) in the city maternity hospital of Bukhara. The average age of the patients was 26.7 ± 1.2 years.